2019
DOI: 10.1111/jnc.14824
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator‐activated receptor gamma participates in the acquisition of brain ischemic tolerance induced by ischemic preconditioning via glial glutamate transporter 1 in vivo and in vitro

Abstract: Glial glutamate transporter 1 (GLT‐1) plays a vital role in the induction of brain ischemic tolerance (BIT) by ischemic preconditioning (IPC). However, the mechanism still needs to be further explained. The aim of this study was to investigate whether peroxisome proliferator‐activated receptor gamma (PPARγ) participates in regulating GLT‐1 during the acquisition of BIT induced by IPC. Initially, cerebral IPC induced BIT and enhanced PPARγ and GLT‐1 expression in the CA1 hippocampus in rats. The ratio of nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…As one of the target genes of PPARγ, GLT-1 is regulated by PPARγ during the acquisition of brain ischemic tolerance ( Romera et al, 2007 ) and is involved in neuroprotection by increasing glutamate uptake in ischemic preconditioning rats ( Zhao et al, 2019 ). Our previous study also found that α-asaronol could promote the mRNA expression of PPARγ in zebrafish ( Jin et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…As one of the target genes of PPARγ, GLT-1 is regulated by PPARγ during the acquisition of brain ischemic tolerance ( Romera et al, 2007 ) and is involved in neuroprotection by increasing glutamate uptake in ischemic preconditioning rats ( Zhao et al, 2019 ). Our previous study also found that α-asaronol could promote the mRNA expression of PPARγ in zebrafish ( Jin et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that ischemic preconditioning (IPC)-induced BIT [ 28 ]. To further explore the role of astrocytes in the process, in this study, cerebral cortical astrocytes and neurons of rats were co-cultured, the astrocytes of the co-cultured cell model pretreated by IPC (45 min of OGD) were subjected to lncRNA high-throughput sequencing (RNA-seq).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that interactions between astrocytes and surrounding cells can influence neuronal activity and brain injury outcomes. [53][54][55][56][57][58] However, the function of astrocytes in EA-induced neuroprotection is unclear. Our previous finding demonstrated that long-term depression induced by endogenous cannabinoids produced neuroprotective effects via astroglial CB 1 R after stroke in rodents, 29 which also indicates that astroglia are of great importance in neuroprotection.…”
Section: Discussionmentioning
confidence: 99%